Beta-cyclodextrin complexing to reduce antibiotic residue in milk - Banala, S.; Brouk, Michael J.; Simmons, S.R.; Schmidt, Karen A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Various percentages (1.2% to 13%) of β- cyclodextrin (β–CD) were added to water or pasteurized whole milk to study β-CD crystallization patterns. Influential factors such as crystallization time (4 to 12 h), crystallization temperature (45º vs. 72ºF), and centrifugation speed (25 to 3000 × g) were investigated. Optimized crystallization conditions were verified in antibiotic-tainted raw milk samples via the enzyme-linked receptor-binding assay and by solids partitioning. In water, β-CD precipitate increased significantly as β-CD concentration and crystallization time increased, but was independent of the centrifugation speed. In pasteurized whole milk, precipitate increased as β-CD concentration, crystallization time, and centrifugation speed increased. The best β-CD precipitation conditions in milk were designated as: 9.1% β-CD concentration (w/w), 4 hour crystallization time, 45ºF, and centrifugation at 25 × g for 10 minutes. Eleven cows were treated with cephapirin sodium or cephapirin benzathine. Milk was obtained 12 h later and treated with β-CD. As β- CD concentrations increased, precipitates increased, and the corresponding supernatants showed reduced concentrations of antibiotics when tested by enzyme-linked receptorbinding assay. Results indicated that β-CD may have the potential to reduce the residues of cephapirin sodium or cephapirin benzathine in antibiotic-tainted raw milk.
Keywords: Dairy; β-cyclodextrin; Cephapirin; Sodium; Cephapirin benzathine; Milk